1976
DOI: 10.1128/jb.126.1.225-231.1976
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase activity in heme-deficient mutants of Staphylococcus aureus

Abstract: Mutants H-14 and H-18 of Staphylococcus aureus require hemin for growth on glycerol and other nonfermentable substrates. H-14 also responds to delta-aminolevulinate. Heme-deficient cells grown in the presence of nitrate do not have lactate-nitrate reductase activity but gain this activity when incubated with hemin in buffer and glucose. Lactate-nitrate reductase activity is also restored to the membrane fraction from such cells by incubation with hemin and dithiothreitol; addition of adenosine 5'-triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We have been concerned with the respiratory nitrate reductase system in wild-type and Hem mutants of Staphylococcus aureus (1,2,7). The reductase in the cytoplasmic membrane links with L-lactate or sn-glycerol-3-phosphate dehydrogenase via cytochrome b, but the organism also has large amounts of cytoplasmic nitrate reductase.…”
mentioning
confidence: 99%
“…We have been concerned with the respiratory nitrate reductase system in wild-type and Hem mutants of Staphylococcus aureus (1,2,7). The reductase in the cytoplasmic membrane links with L-lactate or sn-glycerol-3-phosphate dehydrogenase via cytochrome b, but the organism also has large amounts of cytoplasmic nitrate reductase.…”
mentioning
confidence: 99%
“…Reconstruction of G3P-nitrate reductase activity in mutant H-14. hem mutants of S. aureus, including H-14, fonn apo-cytochrome when grown without hemin; the addition of hemin in vitro to depleted membranes restores apparently normal b-type cytochrome (2). To determine whether G3P-nitrate reductase activity could be reconstituted, heme-depleted membranes with G3P dehydrogenase and nitrate reductase activities were prepared from mutant H-14 after a two-step induction procedure (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that apo-cytochrome is formed by the mutant, which can readily combine in vitro with the heme prosthetic group to reconstitute functional cytochrome. The reconstructed system is also capable of coupling the L-lactate dehydrogenase with nitrate reductase (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in hemerequiring strains of B. melaninogenicus (15), B. ruminicola (5,19), B. fragilis (13), S. aureus (3), and Haemophilus parainfluenzae (18), hemin is utilized for the synthesis of cytochrome of type b or c. We, therefore, investigated whether or not C. pyogenes contains cytochrome(s) and whether the synthesis of such a cytochrome is dependent on the presence of hemin in the medium. Cells were grown aerobically on medium of tryptose broth plus minerals with and without hemin, harvested by centrifugation, and washed three times in ten volumes of potassium phosphate buffer, pH 7.0.…”
mentioning
confidence: 99%